2014
DOI: 10.1523/eneuro.0022-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroids Do Not Modulate TRPM2-Mediated Injury in Females following Middle Cerebral Artery Occlusion

Abstract: TRPM2 is an ion channel that is activated by ischemia in stroke and contributes to neuronal injury only in males. We tested whether the lack of TRPM2 activation following stroke in females is caused by differences in sex steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The mechanism of neuroprotection by female sex steroids is primarily through inhibition of caspase dependent cell death, which is the dominant form of cell death in females (Liu et al, 2009; Liu et al, 2011). Our results obtained with TRPM2 KO demonstrating neuroprotection in male but not female mice are consistent with our previously published observations that activation of TRPM2-mediated cell death following cerebral ischemia is male specific (Jia et al, 2011; Verma et al, 2012; Nakayama et al, 2013; Shimizu et al, 2013; Quillinan et al, 2014). These results demonstrate for the first time male specificity of TRPM2 using genetic knockouts in global ischemia, and are consistent male specific neuroprotection with administration of AGK2 following CA/CPR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mechanism of neuroprotection by female sex steroids is primarily through inhibition of caspase dependent cell death, which is the dominant form of cell death in females (Liu et al, 2009; Liu et al, 2011). Our results obtained with TRPM2 KO demonstrating neuroprotection in male but not female mice are consistent with our previously published observations that activation of TRPM2-mediated cell death following cerebral ischemia is male specific (Jia et al, 2011; Verma et al, 2012; Nakayama et al, 2013; Shimizu et al, 2013; Quillinan et al, 2014). These results demonstrate for the first time male specificity of TRPM2 using genetic knockouts in global ischemia, and are consistent male specific neuroprotection with administration of AGK2 following CA/CPR.…”
Section: Discussionsupporting
confidence: 93%
“…Relevant to the male-specific PARP-mediated cell death pathway, we have recently demonstrated that the calcium-permeable ion channel transient receptor potential channels, M2 (TRPM2) contributes to male-specific injury following cerebral ischemia in a PARP-dependent manner (Shimizu et al, 2013). Inhibition or knock-down of TRPM2 is protective in males, but not females using in vitro and in vivo models of cerebral ischemia (Jia et al, 2011; Verma et al, 2012; Nakayama et al, 2013; Quillinan et al, 2014). A distinguishing property of TRPM2 channels is that they are gated by ADP ribose (ADPr), likely generated following the activation of PARP (Fonfria et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We have taken advantage of this signaling pathway in designing tat-M2NX that targets the ADPr binding pocket of TRPM2, thereby inhibiting its activation. The possibility remains that the lack of effect in females could be due to inadequate dosing of tat-M2NX, though we have performed extensive studies using in vitro neuronal cultures and TRPM2 KO mice in combination with several known TRPM2 channel inhibitors and have never observed a protective effect in female cells or animals (Jia et al, 2011; Verma et al, 2012; Nakayama et al, 2013; Shimizu et al, 2013; Quillinan et al, 2014). Therefore, it is highly unlikely that the lack of protection observed in female mice in the current study using tat-M2NX is related to incorrect dosing.…”
Section: Discussionmentioning
confidence: 99%
“…ADPr is generated by PARP-1 in response to oxidative stress and cerebral ischemia, which is particularly relevant in the setting of reperfusion injury after ischemia (Shimizu et al, 2013). Inhibition of TRPM2 ion channels with clotrimazole (CTZ) or genetic knockdown reduces ischemic injury in males, but not females (Jia et al, 2011; Verma et al, 2012; Shimizu et al, 2013; Quillinan et al, 2014; Shimizu et al, 2016). While we have previously shown that CTZ can be administered up to 2 h after onset of ischemia in stroke models (Shimizu et al, 2013), we have not previously investigated whether inhibiting TRPM2 at more extended time points provides neuroprotection.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of in vivo experiments using this compound is difficult. The sexual dimorphic nature of the effects of clotrimazole on stroke is claimed to be caused by androgen-dependent production of ADPR after an ischemic stroke 66 , although simply administering androgens to females did not cause a TRPM2-dependent increase in cerebral infarct 67 . It should be noted here that clotrimazole is used medically as an anti-fungal compound and is not a selective TRPM2 blocker.…”
Section: Redox Regulation Of Trpm2mentioning
confidence: 99%